Reference domains in master’s dissertations in foreign language didactics - Bouhechiche, Arezki (El Omda in Linguistics and Discourse Analysis, 2023)
In this article, we focus on the study of the following three didactic trends: the linguistic trend, the historical trend, and the praxeological trend. These constitute reference fields in foreign language didactics research. First, we situate them within their historical context and emphasize their principles, criticisms, and the stages of research associated with them. Second, we attempt to identify the fields adopted by students in their master’s dissertations in foreign language didactics defended in 2021.